2007
DOI: 10.1111/j.1745-459x.2007.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Testing and Rinsing Regimens for Toothpastes With Various Cooling and Burn Intensities: Impact on Discrimination and Repeatability

Abstract: Descriptive sensory studies were used to (1) determine the impact of rinsing on residual cooling from strongly mentholated toothpaste and (2) the effect of interstimulus delay on discrimination and repeatability of scores for mint-flavored toothpastes. The panelists brushed their teeth and evaluated residual cooling and burn. In the first experiment, rinsing with crackers and water reduced the time needed to reach a negligible score compared to no rinse or a water only rinse. In the second experiment, samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…A previous study by Allison et al. (2007) has shown that oral rinsing with cracker and water significantly reduced overall cooling and burn intensity, as well as accelerated the decay of residual cooling.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…A previous study by Allison et al. (2007) has shown that oral rinsing with cracker and water significantly reduced overall cooling and burn intensity, as well as accelerated the decay of residual cooling.…”
Section: Resultsmentioning
confidence: 86%
“…1981, 2004; Chambers and Smith 1993; Lotong et al. 2002) and is in the range of highly trained panelists used ( n = 5 – 7) in other recently published papers (Allison et al. 2007; Greene et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In descriptive sensory analysis testing, panelists often are asked to perform several product evaluations in one testing session. Allison et al. (2007) indicated that as many as six toothpaste samples could be tested in one session with reasonable data repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…For each product sampling, toothpaste was served either on a toothbrush or white plastic spoon, depending on the condition selected for evaluation. When the toothpaste was served on a brush, a regular Oral‐B Advantage toothbrush (Oral‐B, Belmont, CA) was selected for its soft, nylon‐rounded bristles, and because it had been used in previously published sensory research (Allison and Chambers 2005; Allison et al. 2007).…”
mentioning
confidence: 99%